Students’ Strategies for Translating Most Frequent English Loanwords in Croatian - Eva Pavlinušić Vilus; Irena Bogunović; Bojana Ćoso (Rasprave Instituta za Hrvatski Jezik i Jezikoslovlje, 2022)
English has become the dominant donor language for many languages, including Croatian. Its prestigious status reduces the likelihood of borrowed words to adapt to a recipient language. As a result, some English loanwords occur in an unadapted form. Recent computational linguistic resources have given the necessary corpus-based data on the frequency and use of English loanwords in Croatian. This paper investigates the strategies employed by 116 students of the Faculty of Maritime Studies, University of Rijeka when asked to translate 392 most frequent, corpus-derived English loanwords into Croatian. The results were then compared with the available corpus-based data. The results show that single-word Croatian equivalents were preferred over adapted forms of English loanwords and multi-word expressions. When no such equivalent was available, unadapted English forms were used more frequently compared to adapted forms and multi-word expressions. The co-existence of loanwords and their native equivalents is reflected in responses to loanwords that have and those that do not have single-word equivalents. The results highlight the need for creating semantically precise single-word native equivalents, at the same time illustrating the resistance to accept novel native words.